COSMOLOGY OF TIME AND THE SPIRITUAL OF LIFE IN JAVANESE-ISLAMIC TRADITION - Ali Jafar (UIN Raden Mas Said Surakarta, 2022)
This study aims to see and analyze the cosmological relation between time and spiritual life in the Javanese-Islamic tradition. Philosophically, the system of pranotomongso(cycle of time) believes to have a solid connection to the knowledge of time and the spiritual dimension of life surrounding it. Based on a study of Javanese literature (primbon)and Islamic views on the cosmology of time, this study shows that in Javanese culture and literature, time is not only seen as a natural cycle but also positioned like living beings. Therefore, the Javanese believe in humans' importance in maintaining good relations with time. The relationship model must be symbiotic-mutualism. At the same time, the Islamic tradition sees that Allah SWT created the universe and the regularity of time for the good of humankind. So, it is clear that both Islamic and Javanese traditions place time as a symbol that indicates the unity of man and his creator. Although time strongly influences human knowledge regarding a time where humans depend entirely on natural cycles, the value of knowledge about time itself is cross-generational.